Design Of A Website-Based Mental Health Early Detection Information System (Case Study: Hu'u Subdistrict) - Wahida, Nurul; Agitha, Nadiyasari; Irmawati, Budi (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2025)
Mental health problems in Hu'u Sub-district are related to the high number of attempted suicides, indicating a lack of access to early detection of mental health disorders. This study aims to design and build a website-based mental health early detection information system to facilitate the early identification of mental health problems in adolescents. The system was developed using the Personal Extreme Programming (PXP) method and the Strengths and Difficulties Questionnaire (SDQ) as a testing instrument. The development process was carried out in two iterations for 30 days. The system was tested using the black box method and User Acceptance Testing (UAT). The results of black box testing show that the system functions correctly and according to the expected functionality. UAT testing involving students and the Rasabou Health Center showed an average score of 90% and 90.04%. These results show that the system is effective in detecting mental health disorders and has met expectations by user needs.